HASTALIK RİSKİNDEN DOLAYI İŞÇİNİN İŞ SÖZLEŞMESİNİ HAKLI NEDENLE FESHİ - (:unkn) unknown (My University, 2014)
İşçi işyerinde hastalanma tehlikesinin bulunması durumunda hem belirli hem de belirsiz süreli iş sözleşmesini derhal feshedebilir. İş Kanununun 24. maddesi I. fıkrasının (b) bendine göre, işçinin sürekli olarak yakından ve doğrudan buluşup görüştüğü işveren yahut başka bir işçinin bulaşıcı veya işçinin işi ile bağdaşmayan bir hastalığa tutulması haklı nedenle fesih sebebidir. İş sözleşmesinin konusu olan işin yapılması işin niteliğinden doğan bir sebeple işçinin sağlığı veya yaşayışı için tehlikeli olursa işçi iş akdini yine haklı nedenle derhal sona erdirebilir (İş K. m.24/I-a). İşyerinde iş sağlığı ve güvenliği önlemlerinin alınmaması halinde de işçi, çalışma koşullarının uygulanmaması nedeniyle İş Kanununun 24. maddesinin II. fıkrasının (f) bendi uyarınca iş sözleşmesini haklı nedenle feshedebilir.

The employee may terminate the employment contract promptly, whet- her for an indefinite period or fixed time, in case of a disease hazard at the workplace. Under 24/ (b) article of the Labour Act, contraction of the emplo- yer, his represantative or another employee who is constantly near the employee and with whom he is in direct contact with an infectious disease or a disease incompatible with his duties is a just cause for termination. The employment contract may be terminated promptly if the performance of the work stipulated in the contract endangers the employee s health or life for a reason which it was impossible to foresee at the time the contract was concluded. The employee may also terminate his employment contract for just cause by virtue of the article 24/ II (f) of the Labour act if the employer fails to implement the conditions of the employment by not observing the occupational health and safety rules.
Emp loyee s Termination of the Emp loy ment Contract with J ust Cause in Case of Disease Hazard
Keywords: Hukuk